Habitação para idosos em São Paulo: século XXI - Souza, Gabriel Bahia Gonçalves de (2019)
In Brazil there are many housing projects for the elderly that are inadequate for the use of these users (Schussel, 2012). Both in terms of accessibility and in relation to design strategies. According to IBGE (2019), the Brazilian elderly population will grow greatly in the coming years, and at this moment, the study and application of housing planning is fundamental to provide health and well-being to our elderly, in order to contribute to our This research investigates the adequacy and inadequacy of three case studies. The first objective of the research is to find out if the 3 Vilas Dignidades (from Avaré, Caraguatatuba and Mogi das Cruzes) that will be analyzed are suitable for the residents. For this, the urban context and the architectural design of each set will be investigated, through Rafael Moneo's book (2013) "Theoretic restlessness and design strategy - In the work of 8 contemporary architects" together with the guidelines of Vila Dignidade (2018) ; (Flório 2002, Ching 2010 and Ching 2010), accessibility check (Brazilian Standards of Accessibility, 2015), and finally, comparisons with Lar Peter Rosegger (Austria, Graz), and Vila of the Elderly (Brazil, São Paulo). Vilas Dignidades are housing complexes developed by the CDHU (Housing Development and Urban Development Company), and they only house independent elderly people (elderly people who do not have difficulties to perform their daily tasks, that is, that they take a bath, cook, and do not depend on caregivers for their basic activities), if they become dependent, are relocated to homes that meet their needs, through the city hall. The second objective of the research is to establish guidelines for strategies of housing projects for the elderly, through the studies of the groups mentioned here, and of several authors who have investigated both the environments of a residence for this public and the planning of housing in their totality, in order to better adapt them.